Implementasi dan Evaluasi Pembelajaran Daring di SDN Perumnas 9 Tangerang - Magdalena, Ina; Kurniawan, Irwan; Rahmayani, Lusy Nur (Lembaga Yasin AlSys, 2022)
This study aims to determine the implementation and evaluation of online learning at SDN Perumnas 9 Tangerang. This type of research is a qualitative descriptive research. The research method used in collecting information is by using observation. The results showed that online learning at SDN Perumnas 9 Tangerang mostly used the WA group application as a medium in providing learning materials and the Quizizz application as a learning evaluation medium. There are several shortcomings in this online learning, such as not all students have Android phones, the background and characteristics of children are different, so it is necessary to evaluate learning as a benchmark for the success of learning. Based on the results of research conducted, online learning is not the best learning method because it is still less effective and difficult to do. Teachers cannot directly assess the development of students. The teacher also cannot see whether the students have understood or not the material that has been delivered.